2015
DOI: 10.1371/journal.pone.0118320
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Bearing and Mobilization in the Postoperative Care of Ankle Fractures: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Cohort Studies

Abstract: PurposeTo determine the effectiveness and safety of interventions used for rehabilitation after open reduction and internal fixation of ankle fractures.MethodsA systematic review and meta-analysis was performed using both randomized trials and cohort studies. The effect of mobilization, weight-bearing, and unprotected weight-bearing as tolerated on postoperative recovery was compared using the Olerud Molander score, return to work/daily activities, and the rate of complications.ResultsA total of 25 articles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 48 publications
2
80
0
Order By: Relevance
“…Ankle fractures are among the most common lower limb fractures and account for 9% of all fractures . There are various classification systems to describe ankle fractures, for example, the AO‐classification, the Lauge–Hanssen classification, and the number of fractured malleoli .…”
mentioning
confidence: 99%
“…Ankle fractures are among the most common lower limb fractures and account for 9% of all fractures . There are various classification systems to describe ankle fractures, for example, the AO‐classification, the Lauge–Hanssen classification, and the number of fractured malleoli .…”
mentioning
confidence: 99%
“…Although a few studies have compared EWB and LWB for surgically stabilized ankle fractures and demonstrated similar functional outcomes, postoperative rehabilitation protocols have largely remained unchanged in today's clinical practice [4,8,11,[19][20][21][22][23][24][25]. Perhaps this relates to a lack of thorough investigation with regards to radiographic parameters other than fracture union when comparing EWB and LWB groups.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ankle fractures is approximately 71-187 per 100,000 people per year and is one of the most common injuries treated by orthopedic surgeons [1][2][3][4][5]. The incidence is likely to increase as the average age of the population rises, as does the amount of participation in sports-related activities [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, other advantages (i.e., prevention of muscle wasting and osteoporosis) are expected. However, these effects have not been investigated thus far [11,12].…”
Section: Discussionmentioning
confidence: 99%